Abortion and Mommy Memoirs: Vilar’s Impossible Motherhood: - Thompson, Mary (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
This essay explores the genre of the mommy memoir for its abortion politics. Buildingon feminist critiques of the genre’s reliance on bio-essentialist ideas of motherhood, Iconsider both the potential and limitations within the genre for representing abortionexperiences. In this essay I analyze Irene Vilar’s Impossible Motherhood:Testimony of an Abortion Addict (2009) for its rhetorical appropriation of themommy memoir form in order to tell a story of reproductive excess.